Syntheses, Structure, Properties, and Chemistry of 1,1-Di(pyrrolyl)ethenes - SENGE, MATHIAS (Royal Society of Chemistry, 1994)
Reaction of a 2-unsubstituted pyrrole with acetic anhydride and stannic chloride unexpectedly promotes self-condensation to give symmetrical di( pyrroly1)ethene as a side-product in &lo% yield, but overall yields of these 1,l-di(pyrro1yl)ethenes can be improved to 66% using a rational alternate route; structure and chemistry of 1 ,I-di(pyrroly1)ethenes 2 are discussed
PUBLISHED
Keywords: Chemistry